O backstage da televisao no Rio Grande do Sul - Reis, Sergio Luiz Puggina (2012)
Being one of the best television Brazilian in the world, maintaining a constant improvement in its over 60 years, this study presents a deeper historical perspective, examining it with a macro view. Recovered sequentially facts, establishing a chronology that facilitates the understanding of the history of television in the Rio Grande do Sul. Thus, this paper shows the main events and also a rescue from the memory of what was done and by whom it was made, highlighting the changing practices of its leaders who have gone through different phases during the 50 years of the television in the state Rio Grande. The approach took place within a qualitative view where we attempted to check how was the relationship between the evolution of television technology ante development and behavioral changes in society affected by it. With the exploratory and qualitative, as we approach the literature, interviews and personal testimonies, besides the exercise of memory. Based on the research problem shows that the specific technical advances of television in Rio Grande do Sul were compatible with the networks of broadcasters heads, kept the proportions of quantitative amount of equipment, for attending to the need of local programming. It shows also the impossibility of a local station financially survive in competition with commercial broadcasters affiliated